Development Trend and Path of Industrial Internet Security Industry in China - Wang Qiuhua (《中国工程科学》杂志社, 2021)
Industrial Internet security is a prerequisite and guarantee for the high-quality development of China’s industrial Internet industry; it is also important for enhancing China’s cyber and manufacturing industries. This study aims at the future development of the industrial Internet security industry in China. First, we analyze the development status of the industry in terms of industrial policies, standards system, industrial structure, and industrial scale. Subsequently, we elaborate on the opportunities and trends of the industry and propose the development path for the next-generation industrial Internet security industry in China. To explore a sustainable development path suitable for China’s industrial Internet security industry, top-level design and policy guidance should be enhanced; technological innovation and transformation should be reinforced; advantages of enterprises and organizations should be complemented to construct a healthy development ecosystem; the security and stability of the supply chain should be emphasized; and personnel training and team building should be promoted to support the research collaboration among government, industry, universities, research institutes, and application.